A Typological Perspective on Latvian Grammar - Kalnača, Andra 1965- (De Gruyter, 2014)
Latvian grammar is a classic Indo-European (Baltic) system with well-developed inflection and derivation. It also bears certain similarities to Finno-Ugric languages. This applies to the mood system and its connections with modality and evidentiality in Latvian. The relations between debitive mood, certain constructions with reflexive verbs and voice in Latvian are intriguing examples of unusual morphosyntactic features
Description based on publisher supplied metadata and other sources
Keywords: Grammatik; Latvian language -- Grammar -- Outlines, syllabi, etc; Latvian language -- Grammar; Latvian language -- Textbooks for foreign speakers -- English; Latvian language; Lettisch